SAR study and conformational analysis of a series of novel peptide G protein‐coupled receptor kinase 2 inhibitors. Issue 1 (25th October 2013) - Gomez‐Monterrey, Isabel; Carotenuto, Alfonso; Cipolletta, Ersilia; Sala, Marina; Vernieri, Ermelinda; Limatola, Antonio; Bertamino, Alessia; Musella, Simona; Grieco, Paolo; Trimarco, Bruno; Novellino, Ettore; Iaccarino, Guido; et al.
ABSTRACT G protein‐coupled receptor kinase 2 (GRK2) plays a central role in the cellular transduction network. In particular, during chronic heart failure GRK2 is upregulated and believed to contribute to disease progression. Thereby, its inhibition offers a potential therapeutic solution to several pathological conditions. In the present study, we performed a SAR study and a NMR conformational analysis of peptides derived from HJ loop of GRK2 and able to selectively inhibit GRK2. From Ala‐scan and d‐Ala point replacement, we found that Arg residues don't affect the inhibitory properties, while a d‐amino acid at position 5 is key to the activity. Conformational analysis identified two β‐turns that involve N‐terminal residues, followed by a short extended region. These information can help the design of peptides and peptido‐mimetics with enhanced GRK2 inhibition properties. © 2013 Wiley Periodicals, Inc. Biopolymers 101: 121–128, 2014.